Reimagining the role of the nursing workforce in Uganda after more than a decade of ART scale-up - Henry Zakumumpa (BMC, 2020)
Abstract Background The expanding roles and increasing importance of the nursing workforce in health services delivery in resource-limited settings is not adequately documented and sufficiently recognized in the current literature. Drawing upon the theme of 2020 as the International Year of the Nurse and the Midwife, we set out to describe how the role of nurses expanded tremendously in health facilities in Uganda during the era of anti-retroviral therapy (ART) scale-up that commenced in June 2004. Methods We employed a mixed-methods sequential explanatory research design. Phase I entailed a cross-sectional health facility survey (n = 195) to assess the extent to which human resource management strategies (such as task shifting) were common. Phase II entailed a qualitative multiple case study of 16 (of the 195) health facilities for an in-depth understanding of the strategies adopted (e.g. nurse-centred HIV care). Descriptive analyses were performed in STATA (v 13) while qualitative data were analysed by thematic approach. Results We found that nurses were the most represented cadre of health workers involved in the overall leadership of HIV clinics across Uganda. Most nurse-led HIV clinics were based in rural settings; however, this trend was fairly even across setting (rural/urban/peri-urban). While 181 (93%) health facilities allowed non-physician cadre to prescribe ART, a number of health facilities (n = 36) or 18% deliberately adopted nurse-led HIV care models. Nurses were empowered to be multi-skilled with a wide range of competencies across the HIV care continuum right from HIV testing to mainstream clinical HIV disease management. In several facilities, nursing cadre were the backbone of ART service delivery. A select number of facilities devised differentiated models of task shifting from physicians to nurses in which the latter handled patients who were stable on ART. Conclusion Overall, our study reveals a wide expansion in the scope-of-practice of nurses during ART scale-up in Uganda. Nurses were thrust in roles of HIV disease management that were traditionally the preserve of physicians. Our study underscores the importance of reforming regulatory frameworks governing nursing workforce scope of practice such as the need for developing a policy on task shifting which is currently lacking in Uganda.